PERMASALAHAN HUKUM PADA KEGIATAN KOPERASI SIMPAN PINJAM DI INDONESIA - Antoni, Veri; Razaga, Azka Farrell (Veritas et Justitia, 2024)
Cooperatives, as key economic actors alongside State/Regional Owned Enterprises and the private sector, have recently come under scrutiny, particularly Savings and Loans Cooperatives (KSPs). Many KSPs have experienced payment failures, leading to legal issues. The widespread defaults in KSPs stem from regulatory gaps; while they engage in activities similar to banks, they are not fully regulated as such. One significant issue is the ineffective supervision of KSPs, many of which receive funds from external investors who are not members. Law on Financial Sector Development and Strengthening has acknowledged the existence of cooperatives that serve non-members (open loop). The Minister of Cooperatives Regulation 8/2003 has addressed past issues and incorporated best practices for banking activities, such as capping deposit and loan interest rates, setting maximum lending limits, business restructuring, and enforcing supervision and reporting standards. However, these regulations do not include provisions for a deposit guarantee institution for cooperatives, which is essential for mitigating the adverse effects of defaults on customers and cooperative members.